2017
DOI: 10.1007/s11356-017-0753-0
|View full text |Cite
|
Sign up to set email alerts
|

Bioagents and silicon promoting fast early upland rice growth

Abstract: Upland rice can overcome major challenges through the insertion of silicate fertilization and the presence of plant growth-promoting microorganisms (PGPMs) during its cultivation, as these factors promote an increase in vigor and plant disease resistance. Two consecutive experiments were conducted to evaluate the beneficial effects of silicon fertilization combined with the PGPM, Pseudomonas fluorensces, Burkholderia pyrrocinia, and a pool of Trichoderma asperellum, in upland rice seedlings, cultivar BRS Prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 53 publications
3
11
0
Order By: Relevance
“…These results are similar to that of Taurian et al (2010). Sousa et al (2017) and Filippi et al (2011) used both PGPRs in a concentration of 10 8 cfu.mL -1 in their studies and showed the results of characterization of the strains application. Thus, the formulations tested appear to be sufficient for increasing the shelf life of the studied bacteria.…”
Section: Shelf Life Evaluation Of Bacterial Formulationssupporting
confidence: 83%
See 1 more Smart Citation
“…These results are similar to that of Taurian et al (2010). Sousa et al (2017) and Filippi et al (2011) used both PGPRs in a concentration of 10 8 cfu.mL -1 in their studies and showed the results of characterization of the strains application. Thus, the formulations tested appear to be sufficient for increasing the shelf life of the studied bacteria.…”
Section: Shelf Life Evaluation Of Bacterial Formulationssupporting
confidence: 83%
“…Excellent results have been obtained in the use of the Brazilian strains, Pseudomonas fluorescens BRM 32111 and Burkholderia pyrrocinia BRM 32113 in experiments performed in vivo and in vitro, including field trials, aiming at both the promotion of growth and the control of rice diseases. The data show suppression of leaf blast and panicle by up to 60 and 33%, respectively, promoting root growth by up to 87% and increasing up to 20% in field productivity (Sousa et al, 2017;Sperandio et al, 2017). Shakih and Sayyed (2015) affirm that commercial success of a bioproduct in suppressing diseases or enhancing plant growth depends on availability and shelf life.…”
Section: Introductionmentioning
confidence: 81%
“…However, in the Si-enriched paddy soil, the estimated PhytOC fluxes were not correlated ( P > 0.05) with these factors. Zhang et al (2014) showed that the yield of rice was increased 14.5% by the use of 225 kg ha -1 Si fertilizer; when the application of Si fertilizer was increased to 375 kg ha -1 , the yield of the rice increased only by 10.1%. Similarly, Wu et al also recommended the use of 225 kg ha -1 Si fertilizer as the most economical measure (Wu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For example, 73% of paddy soils in Zhejiang Province and approximately 60% in Henan Province are Si-deficient (Cai, 2015). Some research has shown that Si fertilizer application can significantly increase the biomass of rice (Wu et al, 2014; Zhang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with traditional rice crops, upland rice has stronger ability of drought resistance and drought tolerance, can adapt to the arid climate, and can greatly save labor and production costs (Kumar and Ladha, 2011;Xia et al 2019). However, up to now, the researches on upland rice mainly focus on the functional genes, genetic diversity and growth promoting microorganisms (Lyu et al 2014;Tuhina-Khatun et al 2015;Ferrari et al 2018;Braga et al 2018;de Sousa et al 2018), and there are few studies on endophytes of upland rice at home and abroad, especially the high-throughput sequencing technology.…”
Section: Introductionmentioning
confidence: 99%